2020
DOI: 10.3389/fphys.2020.596729
|View full text |Cite
|
Sign up to set email alerts
|

Anise Hyssop Agastache foeniculum Increases Lifespan, Stress Resistance, and Metabolism by Affecting Free Radical Processes in Drosophila

Abstract: Anise hyssop, Agastache foeniculum, is a widely used medicinal herb with known antioxidant properties. We studied how dietary supplementation with dried A. foeniculum leaf powder affected physiological and metabolic traits as well as activities of antioxidant enzymes and markers of oxidative stress in Drosophila melanogaster. Dietary hyssop extended the lifespan in a sex and genotype independent manner over a broad range of concentrations up to 30 mg/ml. Dietary supplementation with the herb significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…This extension affected not only the median but also the maximum lifespan. Thus, this study joins others that have already shown a positive effect of algae and plant extracts in the Drosophila model [ 22 , 31 34 ]. To ensure that this is a true pharmacological effect and not a confounder based on reduced food intake, we investigated whether the extract affects food intake.…”
Section: Discussionsupporting
confidence: 81%
“…This extension affected not only the median but also the maximum lifespan. Thus, this study joins others that have already shown a positive effect of algae and plant extracts in the Drosophila model [ 22 , 31 34 ]. To ensure that this is a true pharmacological effect and not a confounder based on reduced food intake, we investigated whether the extract affects food intake.…”
Section: Discussionsupporting
confidence: 81%
“…Excessive nutrition is linked with severe health conditions and an enhanced aging mechanism [ 1 , 6 ]. Although it did not investigate hormetic effects, one particular study showed that anise hyssop ( Agastache foeniculum ) leaf powder extended the lifespan in a sex- and genotype-independent manner, increased fecundity, resistance to oxidative stress and starvation, enzymatic activities of superoxide dismutase, and aconitase, as well as elevated protein in Drosophila [ 45 ]. These results are in line with those obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐day‐old flies were used to measure concentrations of glucose in hemolymph, body glucose, and glycogen levels as described earlier (Strilbytska et al, 2020). Preweighed flies were decapitated, with further centrifugation (3000 g , 6 min, 4°C) to extract hemolymph.…”
Section: Methodsmentioning
confidence: 99%
“…For the determination of Triacylglycerides (TAG) flies were weighted, homogenized in 200 mM PBST (phosphate‐buffered saline containing 0.05% Triton X‐100), boiled, and centrifuged (13,000 g , 10 min) (Strilbytska et al, 2020). The resulting supernatants were used for TAG assay with the Liquick Cor‐TG Diagnostic Kit (Cormay).…”
Section: Methodsmentioning
confidence: 99%